Improving Papuan Students’ Literacy with Small Culture Research-Based Learning - VIANARIKA, FENTY YUNIA VIANARIKA (SEAQIL Journal of Language Education, 2024)
This study evaluates the effectiveness ofResearch Based Learning (RBL) in enhancing English literacyamong Papuan students at SMA Sekolah Anak Indonesia. The primary aim was to address literacy challengesfaced by Papuan students, exacerbated by culturally irrelevant materials and traditional bel iefs that undervalueformal education. Utilizing a mixed method approach, the research combined literature review and analysisof student progress over two academic years (2022 2024). The study focused on 12th grade students’ smallculture research project s related to entrepreneurial activities rooted in Papuan culture. Small culture research,in this context, refers to simple, literature based studies conducted by senior high school students as part oftheir entrepreneur project, focusing on Papuan life tr aditions. Despite economic barriers affecting somestudents, the study concludes that RBL effectively enhances literacy and prepares students for highereducation. Recommendations include increasing financial support, refining educational strategies toacc ommodate diverse student needs, and investing in professional development for educators.